Prospects Of Using Modern Technologies In The Conservation Of Findings In Museum Collection Funds - Noyibjon Maripjonvich Khudoyorov; Samandarbek Sobirjon ugli Ruziboev (Zien Journals, 2024)
The article considers the importance of preserving museum collections and their digitization, as well as the role of modern technologies in museum work. Conservation and digitization processes for preserving museum collections are described, and their long-term preservation and importance for future generations are discussed. Technologies such as digital models, 3D technologies and augmented reality create new opportunities in the preservation and presentation of cultural heritage to the general public
Keywords: Conservation; digital model; digital archiving; 3D scanner